2022
DOI: 10.48048/tis.2022.3464
|View full text |Cite
|
Sign up to set email alerts
|

An Overview: Relationship of Geological Condition and Rainfall with Landslide Events at East Malaysia

Abstract: Tropical country like Malaysia is rich with residual soil and nurtured with high rainfall amount on average 2,550 mm per year. From 2009 until 2018, there are many landslide events reported in the news at Ranau, Sabah and Canada Hill Miri, Sarawak that occurred during rainy season and the landslide recurs within same location over the years. The objective of this study is to determine the relationship of landslide events with geological condition and rainfall at Ranau, Sabah and Canada Hill Miri, Sarawak. Hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Additionally, most of the landslides that occur in Langat River Basin are caused by heavy rain, which occurs most frequently from May to September in the southwest monsoon and from October to March in the northeast monsoon. These findings are consistent with [85,116,117], which found that increasing rainfall intensity throughout the monsoon season will lead to an increase in landslide occurrences. The high intensity of rainfall is frequently related to the slope stability, where it affects the run-off water pressure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, most of the landslides that occur in Langat River Basin are caused by heavy rain, which occurs most frequently from May to September in the southwest monsoon and from October to March in the northeast monsoon. These findings are consistent with [85,116,117], which found that increasing rainfall intensity throughout the monsoon season will lead to an increase in landslide occurrences. The high intensity of rainfall is frequently related to the slope stability, where it affects the run-off water pressure.…”
Section: Discussionsupporting
confidence: 90%
“…Rainfall is the triggering factor that causes landslide occurrences, raising the groundwater level and increasing pore water pressure beneath the surface [82,83]. Over the last decade, previous research has found the presence of an empirical relationship between rainfall and landslide occurrences [84,85]. Rainfall is classified as a natural phenomenon where it is regarded as a potential contributor that significantly impacts the occurrence of landslides [86].…”
Section: Rainfallmentioning
confidence: 99%
“…Based on the fuzzy ANP model dark gray shale formation and based on fuzzy TOPSIS the Lowlevel valley terrace had the highest effect on landslides occurrence while based on the fuzzy ANP model Orbit Olin limestone formation and based on fuzzy TOPSIS the Upper Cretaceous formation had the least effect to landslide occurrence. Rosly et al [87] concluded that the areas that have been covered by shale interbedded with sandstone are more prone to landslide occurrence. In fact, shale has a high amount of clay and is classified as highly plastic soil with increasing pore water pressure from rainfall, the amount of infiltration and consequently matric suction are decreased and finally, the shear strength of the soil is diminished and landslide would be occurred [87].…”
Section: Discussionmentioning
confidence: 99%
“…Rosly et al [87] concluded that the areas that have been covered by shale interbedded with sandstone are more prone to landslide occurrence. In fact, shale has a high amount of clay and is classified as highly plastic soil with increasing pore water pressure from rainfall, the amount of infiltration and consequently matric suction are decreased and finally, the shear strength of the soil is diminished and landslide would be occurred [87].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, these landslides occur on slopes where large amounts of soil mass are moving rapidly. The problem is exacerbated by the rapid development of new infrastructure and housing, which has resulted in a rise in landslides on unstable slopes [9]. This is primarily due to the soil erosion, soil compaction and removal of vegetation caused by human activities [10].…”
Section: Introductionmentioning
confidence: 99%